A Comprehensive Review of Holistic Indicators for Seismic Vulnerability Assessment of Malaysia - Sauti, Noor Suhaiza; Daud, Mohd Effendi; Kaamin, Masiri; Sahat, Suhaila (IIETA, 2023)
Due to the complex nature of seismic vulnerability assessment, different approaches and data are required, based on the country. Alternatively, seismic vulnerability assessment can be categorized into two common techniques, the conventional and holistic methods, the use of which depends on the region’s conditions. Generally, conventional methods concern the consequences of an earthquake by estimating the potential loss caused by the structural inventory damage and the number of casualties. Meanwhile, holistic methods focus on the different primary factors that contribute to seismic vulnerability, which are represented by the social, economic, physical, and environmental elements of a community or structure in a region. However, less attention has been given to the quantitative evaluation of holistic seismic vulnerability in Malaysia compared to hazardrelated research. Therefore, the aim of this study was to identify the holistic seismic vulnerability indicators in the context of an earthquake in Malaysia. Analysis is critical for understanding the numerous indicators of causes of earthquakes to define their relative relationships and the disaster risk probability. Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting method, a comprehensive review of the Scopus and Web of Science databases was undertaken to search for indicators with a substantial impact on the aforementioned dimensions of earthquake vulnerability. This article concludes that there are three major elements of vulnerability (exposure, resilience, and coping capacity), comprising eighteen indicators of seismic vulnerability, in the context of earthquakes in Malaysia.